EVALUASI PENERAPAN PROTOKOL KESEHATAN DALAM MENCEGAH PENULARAN COVID-19 DI GEREJA-GEREJA WILAYAH KECAMATAN GUDO KABUPATEN JOMBANG TAHUN 2021 - Lois Putu Primawidani; Ferry Kriswandana; Deddy Adam (Poltekkes Kemenkes Surabaya, 2022)
In March 2020 the government determined that the COVID-19 outbreak was a national disaster that spread through splashes, so gatherings of large numbers of people could increase the risk of spreading COVID-19. The church is a place for Christians to carry out religious activities. During this activity, there was interaction between congregations that could increase the potential for the spread of COVID-19. The purpose of this study was to describe and evaluate the application of health protocols in preventing the transmission of COVID-19 in churches in the Gudo District, Jombang Regency in 2021.This study uses a descriptive observational method. The variables of this research are socialization and education of COVID-19 health protocols, use of masks, hand washing facilities or hand sanitizers, disinfection, social distancing systems, thermoguns, restrictions on the number of congregations and duration of worship, as well as air circulation and floor types. Data collection used observations and interviews to describe the implementation of the COVID-19 health protocol in seven churches in Gudo District, Jombang Regency. Data analysis in this study is to collect data, process and compile, then presented in tabulation then each variable is analyzed descriptively.Observation results show that all churches get the Good category with a minimum score of 76.92%. The results of the interview show that the manager has facilitated the congregation in implementing the COVID-19 health protocol.The conclusion from this research is that the implementation of the COVID-19 health protocol is not optimally implemented, namely socialization and education of the COVID-19 health protocol and measuring body temperature. Suggestions for other researchers who want to continue this research are researching the implementation of the COVID-19 health protocol in places of worship using quantitative research methods.